THE EFFECTIVENESS COMPARISON BETWEEN INQUIRY AND PROBLEM BASED LEARNING TOWARDS GEOGRAPHY LEARNING OUTCOMES - Upang Septa Putra; Muhsinatun Siasah Masruri (Department of Geography Education, University of Jember, 2019)
This study aims to determine the differences of learning outcomes between students that were performed using inquiry and student who were applied using problem based learning in classes of X SMA 2 Plakat Tinggi. This study also purposes to examine the effectiveness comparison between problem based learning and inquiry method. The research engages quantitative research with quasi-experimental type. Subject selection conducts match design. The population of this study were students of class X IPS in SMA 2 Plakat Tinggi which composed of three classes. The sample selection in this study engaged purposive sampling, hereby X IPS 3 was elected as experimental group 1 (Problem based learning) and class X IPS 1 as the experimental group 2 (Inquiry) class. Data collection technique performed in this study was learning outcomes in the form of written test. Data analysis technique was engaging independent sample t-test, which was followed by N increased and effect size extent. The findings are differences of learning outcomes improvement between students who studied utilizing inquiry method and students who were taught using problem based learning method. Problem based learning is more effective than inquiry in promoting Geography learning outcomes. This is indicated through calculation result upon effect size extent, where students who were taught using problem based learning method obtain a value of 4.185, larger compared to those who were treated using inquiry method which obtain a value of 3.462. Keywords: Inquiry, problem based learning, Geography References Agustini, D. M. (2017). PBL untuk Meningkatkan Hasil Belajar IPA Siswa Tunarungu Kelas IV A SLBN 2 Bantul. Widia Ortodidaktika, 6(4), 427-437. Alberta. (2004). Focus on Inquiry: A Teacher’s Guide to Implementing Inquiry Based Learning. Canada: Learning Resources Centre. Barret, T., & Moore, S. (2010). New Approaches to: Problem based learning Reveitalising Your Practice in Higher Education. New York: Routledge. Blessinger, P., & Carfora, J. M. (Eds.). (2014). Inquiry-based learning for the arts, humanities and social sciences: A conceptual and practical resource for educators. Emerald Group Publishing. Bridges, S., McGrath, C., & Whitehill, T. L. (Eds.). (2012). Problem-based learning in clinical education: The next generation (Vol. 8). Springer Science & Business Media. Chu, S. K. W., Reynolds, R. B., Tavares, N. J., Notari, M., & Lee, C. W. Y. (2017). 21st Century Skills Development Through Inquiry-Based Learning. doi:10.1007/978-981-10-2481-8 Cohen J. (1988). Statistical Power Analysis for the Behavioral Sciences. New York, NY: Routledge Academic. Duran, M., & Dokme, L. (2016). The Effect of the Inquiry Based Learning Approach on Student’s Critical Thinking Skills. Eurasia Journal of Mathematics, Science & Technology Education, 12(12), 2887-2908. https://doi.org/10.12973/eurasia.2016.02311a. Friesen, S., & David, S. (2013). Inquiry Based Learning Review. Calgary: University of Calgary. Retrieved from https://www.researchgate.net/publication/312592892_Inquiry-Based_Learning_A_Review_of_the_Research_Literature. Goodman, D. (2018). Problem-Based Learning in the MPA Curiculum. Journal of Public Affrairs Education, 14(2), 253-270. Retrieved from http://www.jstor.org/stable/40215813. Grady, G.O., Elaine H.J.Y., Karen, P.L.G., & Henk, G.S. (2012).One Day One Problem an Approach to Problem Based Learning. Singapore: Springer. Handoyono, N.A. (2016). Pengaruh Inquiry Learning Dan Problem-Based Learning terhadap Hasil Belajar PKKR Ditinjau dari Motivasi Belajar. Jurnal Pendidikan Vokasi, 6(1). http://dx.doi.org/10.21831/jpv.v6i1.8114. Hmelo-Silver, C. E. (2004). Problem-based learning: What and how do students learn?. Educational psychology review, 16(3), 235-266. McKeown, T. R., Abrams, L. M., Slattum, P. W., & Kirk, S. V. (2015). Enhancing Teacher Beliefs through an Inquiry-Based Professional Development Program. Journal of Education in Science, Environment and Health, 2(1), 85. doi:10.21891/jeseh.30143 Minner, D. D., Levy, A. J., & Century, J. (2010). Inquiry-based science instruction-what is it and does it matter? Results from a research synthesis years 1984 to 2002. Journal of Research in Science Teaching, 47(4), 474–496. doi:10.1002/tea.20347 Mundilarto. (2013). Keefektifan Pembelajaran Inquiry Based Learning untuk Peningkatan Karakter Siswa pada Pembelajaran Fisika. Jurnal Cakrawala Pendidikan. Retrieved from https://journal.uny.ac.id/index.php/cp/article/download/1483/pdf. Seng, T.O. (2009). Problem Based Learningand Creativty. Singapore: Cengage Learning Asia Pte Ltd. Simone, C.D. (2014). Problem Based Learning in Teacher Education: Trajectories of Change. International Journal of Humanities and Social Science, 4(12).Retrieved from http://www.ijhssnet.com/journals/Vol_4_No_12_October_2014/3.pdf. Smith, R.S., & Walker, R. (2010). Can Inquiry-Based Learning Strengthen the Links between Teaching and Disciplinary Research? Studies in Higher Education, 35(6), 723-740. https://doi.org/10.1080/03075070903315502. Sumaatmadja, N. (2001). Metode Pengajaran Geografi. Jakarta: BumiAksara. Suprijono, A. (2015). Cooperative Learning Teori & Aplikasi Paikem. Yogyakarta: Pustaka Pelajar Trianto. (2010). Model Pembelajaran Terpadu: Konsep, Strategi, dan Implementasinya dalamKurikulum Tingkat Satuan Pendidikan (KTSP). Jakarta: Bumi Aksara. Unver, A.O., & Sertac, A. (2011).Ovierviews on Inquiry Based and Problem Based Learning Methods. Western Anatolia Journal of Educational Science, 303-309. Retrieved from http://webb.deu.edu.tr/baed/giris/baed/ozel_sayi/303-310.pdf. Warner, R.M. (2008). Applied Statistic. USA: Sage Publications. Westwood, P.S. (2008).What the Teacher Need to Know About Teaching Methods. Camberwell, V: Acer Press. Whitcombe S.W. (2013) Problem-based Learning Students’ Perceptions of Knowledge and Professional Identity: Occupational Therapists as ‘Knowers’, British Journal of Occupational Therapy,76(1), 37-42 Wijayanti, A., & Wulandari, T. (2016). Efektivitas Model CTL dan Model PBL terhadap Hasil Belajar IPS. Harmoni Sosial: Jurnal Pendidikan IPS, 3(2), 112. doi:10.21831/hsjpi.v3i2.7908 Yew, E.H.J., & Karen, G. (2016). Problem-Based Learning: An Overview of its Process and Impact on Learning. Journal Health Professions Education, 2(2), 75-79. https://doi.org/10.1016/j.hpe.2016.01.004Ẏuniawati. (2016). Peningkatan Kualitas Pembelajaran PPKN Melalui Penerapan Problem Based Learning di SMP. Jurnal Pendidikan IPS. Retrieved from https://journal.uny.ac.id/index.php/hsjpi/article/view/7947/8576. Copyright (c) 2019 Geosfera Indonesia Journal and Department of Geography Education, University of Jember This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License